2016
DOI: 10.1159/000452567
|View full text |Cite
|
Sign up to set email alerts
|

High Uric Acid Activates the ROS-AMPK Pathway, Impairs CD68 Expression and Inhibits OxLDL-Induced Foam-Cell Formation in a Human Monocytic Cell Line, THP-1

Abstract: Background/Aims: Hyperuricemia is part of the metabolic-syndrome cluster of abdominal obesity, impaired glucose tolerance, insulin resistance, dyslipidemia, and hypertension. Monocytes/macrophages are critical in the development of metabolic syndrome, including gout, obesity and atherosclerosis. However, how high uric acid (HUA) exposure affects monocyte/macrophage function remains unclear. In this study, we investigated the molecular mechanism of HUA exposure in monocytes/macrophages and its impact on oxidize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 45 publications
3
26
0
Order By: Relevance
“…Previous studies suggested that hyperuricemia was a risk factor for the poor outcomes [30] and through the following pathway: (1) insulin resistance [39]; (2) increasing the risk of hypertension and further aggravated atherosclerosis [40]; (3) impair the selfregulation of the arteriole [41]; (4) UA induces cardiomyocyte apoptosis through activation of calpain-1 and endoplasmic reticulum stress [42]. Furthermore, high UA exposure activated the ROS-AMPK pathway, impaired CD68 expression [43], and induced oxidative damage and inhibited the viability of cardiomyocytes by activating ERK/p38 signaling [44]. The neuroprotective function of SUA can be explained from the following aspects.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggested that hyperuricemia was a risk factor for the poor outcomes [30] and through the following pathway: (1) insulin resistance [39]; (2) increasing the risk of hypertension and further aggravated atherosclerosis [40]; (3) impair the selfregulation of the arteriole [41]; (4) UA induces cardiomyocyte apoptosis through activation of calpain-1 and endoplasmic reticulum stress [42]. Furthermore, high UA exposure activated the ROS-AMPK pathway, impaired CD68 expression [43], and induced oxidative damage and inhibited the viability of cardiomyocytes by activating ERK/p38 signaling [44]. The neuroprotective function of SUA can be explained from the following aspects.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress injury has been reported to be involved in pancreatic β-cell injury induced by uric acid. It has been confirmed that uric acid can inhibit cell proliferation and increase oxidative stress, and subsequently inhibit insulin secretion by activating the reactive oxygen species (ROS)/adenosine monophosphate-activated protein kinase (AMPK)/ extracellular signal-regulated kinase (ERK) pathways [14][15][16][17][18]. Likewise, a previous study performed in pancreatic β cells has demonstrated uric acid triggers inhibition of oxidative stress and growth through activations of the AMPK and ERK signal pathways [17].…”
Section: Introductionmentioning
confidence: 92%
“…ROS are generally believed to be harmful to cells and tissues [13]. HUA levels increase oxidative stress in multiple cells [14][15][16][17][18] and cause damaged endothelia, renal injury, insulin resistance and inflammation. The three members of the mitogen-activated protein kinase (MAPK) family, extracellular signal-regulated kinase (ERK), c-Jun N-terminal kinase (JNK) and p38, regulate a variety of physiological processes, such as cell growth, metabolism, differentiation and cell death.…”
Section: Introductionmentioning
confidence: 99%